(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the methodology for compiling the HSG idiomatic dictionary. The main attention is paid to the criteria for choosing idioms, methods of data collection and analysis, as well as comparing the HSG dictionary with other idiomatic dictionaries. The results of the analysis made it possible to identify the unique features of the HSG methodology and offer recommendations for improving approaches to the compilation of idiomatic dictionaries. In conclusion, the limitations of the current study and the prospects for further development are discussed research in this area.